2018
DOI: 10.3389/fimmu.2018.00614
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Type I Interferons by Therapeutic Nanoparticle-Based Vaccination Is Indispensable to Reinforce Cytotoxic CD8+ T Cell Responses During Chronic Retroviral Infection

Abstract: T cell dysfunction and immunosuppression are characteristic for chronic viral infections and contribute to viral persistence. Overcoming these burdens is the goal of new therapeutic strategies to cure chronic infectious diseases. We recently described that therapeutic vaccination of chronic retrovirus infected mice with a calcium phosphate (CaP) nanoparticle (NP)-based vaccine carrier, functionalized with CpG and viral peptides is able to efficiently reactivate the CD8+ T cell response and improve the eradicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…This is well in line with our previous results from mouse models and could be due to the enhanced delivery of the ligands to endosomal compartments, where TLR 3 and TLR 9 are located [16,20]. IL-12, IL-2, IFN-α, and TNFα are very important for the sufficient activation of effector CD8 + T cells [19,[31][32][33] or in an autocrine manner for enhanced DC function [34]. Therefore, this is an optimal prerequisite for effective T cell priming.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is well in line with our previous results from mouse models and could be due to the enhanced delivery of the ligands to endosomal compartments, where TLR 3 and TLR 9 are located [16,20]. IL-12, IL-2, IFN-α, and TNFα are very important for the sufficient activation of effector CD8 + T cells [19,[31][32][33] or in an autocrine manner for enhanced DC function [34]. Therefore, this is an optimal prerequisite for effective T cell priming.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, analysis at an earlier time point might show stronger differences regarding costimulatory molecule expression. Concentrations of the TLR ligands were adjusted from in vivo data that was generated previously [17,19]. Lower concentrations of NPs or TLR ligands might also emphasize the advantage of CaP NPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have demonstrated that reactivation of virusspecific CD8 þ T cells with functionalized CaP nanoparticles is dependent on IFN I during therapeutic vaccination of chronically infected mice (24). In this study, CpG was identified as driving force of IFN I release.…”
Section: Type I Ifns Are Essential For the Antitumor Response Inducedmentioning
confidence: 82%
“…Nanoparticle vaccines delivering FV antigen and molecules for TLR stimulation were able to induce potent T cell responses that restricted chronic FV infection (Knuschke et al 2014). This successful therapeutic vaccination was dependent on type I IFN induction (Knuschke et al 2018) and could be further improved by Treg depletion (Knuschke et al 2016).…”
Section: Immunotherapies In Fv Infectionmentioning
confidence: 99%